Persepsi atlet sepak bola remaja terhadap pemberian sport massage - Muhammad Syahlan Thoyyiby; Z. Arifin; Asep Angga Permadi (Jurnal Porkes, 2026)
This research was motivated by the limited studies on adolescent soccer athletes' perceptions of sport massage as a recovery method, despite adolescent athletes being in a crucial phase of sports development. This study aims to describe adolescent soccer athletes' perceptions of sport massage, particularly regarding physiological benefits, muscle flexibility and endurance, psychological conditions, and post-exercise recovery processes. The study employed a quantitative descriptive approach with a survey method. The population was adolescent soccer athletes of the Persigar U15 club, with a sample of 30 athletes selected using total sampling technique. The instrument was a 30-item questionnaire using a four-point Likert scale. Data analysis used percentage calculations and descriptive statistics. The results showed a total score of 2932 out of a maximum of 3600 (81.44%), with percentages of strongly agree at 44.88% and agree at 41.33%. The Cronbach's Alpha reliability test yielded a value of 0.86. This study concludes that adolescent soccer athletes' perceptions of sport massage fall into the very good category. Sport massage is perceived as beneficial for reducing muscle fatigue, increasing relaxation, and supporting athletes' physical and mental readiness.